Characterization of sludge drawn from sewage treatment plants based on tertiary treatment process at Dal lake, Srinagar, J & K, India - ul-Solim2, Bilal Ahmad Mir1, Amit Pal1* and Sabah- (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The aim of this work was to determine characteristics of the sewage sludge drawn from sewage treatment plants Laam, Habbak and Hazaratbal located at the bank of world famous Dal Lake, Srinagar. Analysis of the sludge showed that the major matrix elements were organic carbon, available nitrogen with significant percentage of available micro elements (Zn, Cu, Mn and Fe) although available phosphorous was also present in substantial amounts. The results showed increase in percentage of micro and macro nutrients in the sewage sludge during peak winter due to harsh climate prevailing in the valley which decreases the efficiency of secondary treatment of moving bed bioreactor sewage treatment plants. Moreover the sewage treatment plant of Laam shows increase in efficiency due to the diluted and low inflow of sewage coming to the sewage treatment plant. The Hazaratbal sewage treatment plant shows higher micro and macro nutrients due to the large catchments area which leads to the concentrated sewage inflow to the sewage treatment plant. Results showed that the organic carbon was found in significant percentage to be used for improving the soil physical characteristics. Among the DTPA extractable micro nutrients, Fe was present in dominant concentration although the Zn, Cu and Mn were present in sufficient quantity. Ã‚Â 